All the President's men ; Looking back at the Cory years ; Covering the presidency [videorecording]. - Aquino, Corazon Cojuanco 1933-.; Lazaro, Cheche; Ramos, Fidel Valdez 1928-. (Quezon City Probe Productions, 1993)
A look at the men who occupy major Cabinet positions in the administration of Fidel Ramos and Corazon Aquino; the men in media tasked to cover the President; and the members of the Presidential Coverage Team, Radio Television Malacanang tell their story.
Contents : All the president's men (18 min.) -- Looking back at the Cory years (21 min.) -- Covering the presidency (16 min.)
VHS
Keywords: Ramos administration; Aquino administration; Journalists -- Philippines -- Correspondence, reminiscence, etc; Press and politics -- Philippines